Personality and the agent’s performance in multilevel marketing mediated by interpersonal identification - Shaierah Gulabdin; Toh, Pei Sung; Stephen Laison Sondoh Jr. (Asian Scholars Network, 2020)
This paper aims to explore the influence of personality traits on the agent’s performance in the MLM industry based in Malaysia, taking into consideration the mediating role of interpersonal identification. Method or approach used is the Big Five Factors (BFF) of personality traits used in this paper. Previous research and literature reviewed to establish current practices and point to gaps to be filled with meeting the market needs. This paper proposed an interpersonal identification as a mediating factor of the agent’s performance. Findings of this study are the Multilevel Marketing (MLM) industry faces challenges in attracting and maintaining agents in their roles. The big five factors alone cannot adequately explain agents. The agent’s interpersonal identification can play a significant mediating role in the big five-factor framework in predicting the agent’s performance. Industry and academia need to work collaboratively to educate the general public on the rewards and benefits of working in the MLM industry. As a practical implication, adopting strategies described in this study may contribute to social change by increasing the success rate among multilevel marketers, thus reducing unemployment, and producing a positive effect on the economy. This paper adds value and contributes to the MLM industry and academia, as it represents current research and thought processes from both the academic community and the practitioners (sales managers, executives, supervisors, human resources managers). The proposed framework in this paper helps the researcher by providing a tool for systematic evaluation and testing of the real empirical situation of the agent’s performance.